1999
DOI: 10.1002/lt.500050607
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure associated with prolonged use of bromfenac leading to liver transplantation

Abstract: , § and the Acute Liver Failure Study GroupBromfenac, a nonnarcotic analgesic nonsteroidal anti-inflammatory drug, was associated with reversible, minor elevations in serum aminotransferase levels during clinical trials. The aim of this study is to describe the clinical, laboratory, and histological features of 4 patients with severe bromfenac hepatotoxicity identified at 3 tertiary care centers participating in the US Acute Liver Failure Study Group. Bromfenac was administered for chronic musculoskeletal diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Nonetheless, these findings raise some important questions that warrant further investigation. Although no systemic adverse effects have been associated with the ophthalmic use of bromfenac sodium to date, it has only recently been made available for ophthalmic use and rare cases of idiosyncratic hepatotoxicity have been associated with the long-term use of oral bromfenac [36][37][38][39] . Idiosyncratic hepatotoxicity is an unpredictable, immune-mediated response that is not dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these findings raise some important questions that warrant further investigation. Although no systemic adverse effects have been associated with the ophthalmic use of bromfenac sodium to date, it has only recently been made available for ophthalmic use and rare cases of idiosyncratic hepatotoxicity have been associated with the long-term use of oral bromfenac [36][37][38][39] . Idiosyncratic hepatotoxicity is an unpredictable, immune-mediated response that is not dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common class of drugs implicated is the nonsteroidal anti-inflammatory drugs [24 ] including several that have been removed from the market such as bromfenac [25]. An epidemiologic study conducted in Spain and France found disparate incidences in the two countries that could possibly be explained by different patterns of drug use or by variation in the data collection techniques [26].…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 98%
“…Despite these efforts, the manufacturer and the FDA continued to receive reports of severe injuries, including reports of death or need for liver transplantation (Moses and Schroeder et al 1999;Hunter and Johnston et al 1999;Rabkin and Smith et al 1999;Fontana and McCashland et al 1999). Given the availability of other effective NSAIDs, bromfenac was withdrawn from the market in June 1998.…”
Section: Duract (Bromfenac)mentioning
confidence: 99%